2009
DOI: 10.3354/meps07911
|View full text |Cite
|
Sign up to set email alerts
|

Movement of gray snapper Lutjanus griseus among subtropical seagrass, mangrove, and coral reef habitats

Abstract: Many fishes are thought to make diel, seasonal and/or ontogenetic migrations among seagrass, mangrove, and coral reef habitats. However, most evidence of such movement has been inferred from density and size structure differences among these habitats in tropical waters. The aim of the present study was to directly evaluate multiple habitat use by an ecologically and economically important reef fish, the gray snapper Lutjanus griseus, in subtropical waters. An integrated set of activities was conducted, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
80
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 113 publications
(89 citation statements)
references
References 30 publications
7
80
2
Order By: Relevance
“…58 and 59 corresponded to spawning movements; further research into the importance of the Tortugas NTMRs for spawning yellowtail snapper is recommended. Consistent with observations by Moe (1972) and Luo et al (2009), a tagged gray snapper made routine nocturnal migrations between site B19 (see Fig. 1C) and presumed foraging habitats west of the array, possibly outside the RNA.…”
Section: Discussionsupporting
confidence: 73%
“…58 and 59 corresponded to spawning movements; further research into the importance of the Tortugas NTMRs for spawning yellowtail snapper is recommended. Consistent with observations by Moe (1972) and Luo et al (2009), a tagged gray snapper made routine nocturnal migrations between site B19 (see Fig. 1C) and presumed foraging habitats west of the array, possibly outside the RNA.…”
Section: Discussionsupporting
confidence: 73%
“…A tagging study by Kaunda-Arara & Rose (2004) showed that adult L. fulviflamma swam distances up to 2 km, confirming that this species is capable of migrating between coral reefs and seagrass beds. Feeding migrations from coral reefs to adjacent seagrass beds have been documented for other snappers in the Florida Keys, USA (Luo et al 2009), and in the US Virgin Islands (Hitt et al 2011). The lack of potential food items from Mafia coral reefs in our study, however, limit our results, and further studies, tagging and following large individuals on coral reefs, are needed to confirm feeding migrations between coral reefs and seagrass beds by L. fulviflamma.…”
Section: Feeding Migrationscontrasting
confidence: 45%
“…This is further supported by studies from Bahamian waters documenting that lemon sharks, one of the main predators identified in our study, tend to focus search efforts near the mangrove shoreline (Morrissey & Gruber 1993, Franks 2007. Recent acoustic tracking of gray snapper in Biscayne Bay (Luo et al 2009) also indicates that the snappers may avoid foraging near the mangroves at night. At sunset, gray snapper migrate rapidly out of the mangroves in a synchronized fashion and do not forage in seagrass nearest the mangroves, but rather move as much as 500 m offshore, before returning to the same mangrove proproots the following morning (Luo et al 2009).…”
Section: Discussionmentioning
confidence: 99%